The Combined Platysma And Temporalis Flap: An Alternative Method Of Reconstructing The Cheek Defect - Mustafa, Wan Mahadzir; Adnan, Khairulzaman bin (IIUM Medical Journal Malaysia, 2017)
Introduction: Reconstruction of the primary defect following resection of primary tumour is part of the surgical treatment of head and neck cancer. The present paper reports a case of reconstruction of medium size through and through defect of the cheek with the transverse platysma myocutaneous flap combined with the temporalis flap. Materials and Methods: A 78 years old Chinese male with presented with biopsy proven squamous cell carcinoma of the cheek mucosa. After excision a medium size (about 4cm by 5cm) through and through defect of the cheek was present. A posteriorly based platysma flap and temporalis flap was harvested and used to reconstruct the defect. The donor site was closed primarily. Results: Overall aesthetic results was good. There was no necrosis of flap, dehiscence or fistula. Flap contracture was the main complication. Conclusion(s): The combined platysma and temporalis flap is a good method to reconstruct a medium sized through and through defect of cheek.